How work discipline and leadership influence employees’ performance? - Matthew W. McCarter; M. Ikhwan Maulana Haeruddin; Muhammad Yushar Mustafa; Rahmat Riwayat Abadi; Khaidir Syahrul (International Journal of Educational Administration, Management, and Leadership, 2022)
This study aims to determine the effect of work discipline and leadership style on employee performance at hotels in Texas. The analysis used in this study using multiple regression analysis. The population in this study were all employees at the hotels. Sampling in this study was carried out using a sampling technique, namely saturated sampling, so the number of samples was 300 employees who were recruited as samples in the study. The results of the study after the data were processed with SPSS.21 with the analytical method used in this study, namely multiple linear regression analysis, Ftest, Ttest, and coefficient of determination (R2). Based on the results of the study it was found that there was a positive and significant effect of work discipline and leadership style variables on employee performance at the hotels simultaneously. This is evidenced by the value of Fcount which is greater than the value of Ftable (29.288 > 3.32) and the probability value which is smaller than (0.000 < 0.05). While partially there is a positive and significant effect of work discipline on employee performance and leadership style has a negative and significant effect on employee performance at the hotels in Texas. Where the tcount value is greater than the ttable value (1,703). The work discipline variable has a tcount value of 5.799 (p = 0.000) and the leadership style variable has a tcount value of -5.035 (p = 0.000). The variable that has the most dominant influence on employee performance at the hotels in Texas is the work discipline variable with the largest tcount value (5.799).